Bee Pollen: Chemical Composition and Potential Beneficial Effects on Health - P. F. Guine, Raquel (Current Nutrition & Food Science, 2015)
Since long ago, bee pollen has gained reputation as an important source of energy and beneficial substances from the nutritional and health points of view. However, in the recent years this natural product has gained much interest, either from the scientific community, increasing the number of works about it, or from the general population, that buy it as natural functional food. This review intends on one hand to focus on the chemical composition of the bee pollen, since it is the chemical components that provide it with beneficial properties. On the other hand, it also addresses the health effects of this product, by referring the different studies that have been done and published this theme. From the information found on the literature it was possible to depict some of the most investigated effects of bee pollen, such as antimicrobial, anti-inflammatory, antioxidant and antimutagenic activities.
Keywords: Apis meliffera